The influence of overall treatment time to the efficiency of chemo-radiotherapy for locally advanced cervical cancer - Tharavichitkul E. (2017)
© Cambridge University Press 2017 Purpose: This study aims to clarify the influence of overall treatment time (OTT) on the efficiency of combined chemo-radiotherapy in cervical cancer. Material and methods: This retrospective study enrolled 122 cervical cancer patients who had squamous cell carcinoma and had undergone definitive chemo-radiotherapy from 2009 to 2013. All patients received whole pelvic radiotherapy (WPRT) with the dose of 50 Gy in 25 fractions (with central shielding after 44 Gy) plus intracavitary brachytherapy with the dose of 28 Gy in four fractions. During WPRT, all patients received concurrent chemotherapy with weekly platinum-based regimen. The data of patient characteristics, OTT, treatment results and toxicities were collected and evaluated. Results: The mean follow-up time was 36 months. The mean age of patients was 52 years old; 68% of patients were stage IIB related to International Federation of Gynaecology and Obstetrics staging. Pelvic control (PC), distant metastasis-free survival (DMFS), disease-free survival (DFS) and overall survival (OS) rates did not differ significantly in the data-derived cut points of 55·8 and 53 days. No statistically significant difference in treatment results between the two groups of OTT < 49 and OTT≥62 days was observed. Conclusions: In our data-derived cut point, OTT did not influence to PC, DMFS, DFS and OS. The influence of OTT on treatment results may be found in longer periods.